Implementasi Hukum Kewarisan Islam dalam Masyarakat Adat Bugis di Sulawesi Selatan: Antara Syariat dan Tradisi - Nur Aisyah; Nur Amalia; Salsa Sahlat; Rasdiyanah Audiah Syarif (Program Studi Hukum Keluarga Islam (HKI) dan bekerjasama dengan Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2026)
This study analyses the implementation of Islamic inheritance law within the Bugis indigenous community in South Sulawesi, highlighting the relationship between Islamic sharia and local traditions. The study employs a qualitative approach, specifically library research, through the analysis of various relevant primary and secondary sources. The findings indicate that the practice of inheritance law among the Bugis community reflects legal pluralism, in which the principles of Islamic inheritance coexist alongside customary values such as pangadereng, tudang adeq, and siri’. Customary law functions as a mechanism for deliberation and social legitimisation in the distribution of inheritance without disregarding the provisions of Sharia. The implementation of inheritance law is also influenced by factors such as education, gender, social stratification, migration and modernisation. Therefore, it is necessary to strengthen the synergy between Islamic law and customary law through the maqāṣid al-syarī‘ah approach, to improve education on family law, and to strengthen the role of customary and religious leaders in order to achieve fair, harmonious and equitable inheritance settlements that are in line with the values of Bugis society.